Anthropometric study of nasal index of Bali Aga population - Agus Rudi Asthuta; I Putu Yupindra Pradiptha (PERHATI-KL, 2019)
Background: Anthropometry is the measurement of human and more inclined to focus on the dimensions of the human body. Nasal indexes can be used to help determine personal identity, especially race, ethnic and gender differences. Purpose: The general objective of this study was to find out the results of nasal index anthropometric studies on Bali Aga populations in Tenganan. Methods: In this study, 20 samples (4 male and 16 female) within age group of 17-30 years old of Bali Aga population in Tenganan Village were measured strictly on Frankfort’s plane with the help of a sliding caliper. Results: The results of nasal anthropometry measurements obtained an average width of the nose of 38.790 mm, the average nose length of 45.490 mm and nasal index measurements obtained an average of 85.6416. Conclusion: Nasal index can be used to help determine personal identity, especially race, ethnic and gender differences. The result of nasal index in Bali Aga population in Tenganan Village is the Platyrrhine nose (wide nose). Latar belakang: Antropometri adalah pengukuran manusia dan lebih cenderung terfokus pada dimensi tubuh manusia. Nasal indeks dapat digunakan untuk membantu menentukan identitas personal, terutama perbedaan ras, etnis, dan jenis kelamin. Tujuan: Tujuan umum penelitian ini adalah untuk mengetahui hasil studi antropometri nasal index pada populasi Bali Aga di Tenganan. Metode: Studi ini melibatkan, 20 sampel (4 laki-laki dan 16 perempuan) dari penduduk Bali Aga Desa Tenganan yang diukur pada Frankfort’s plane dengan bantuan jangka sorong. Hasil: Pada hasil pengukuran antropometri hidung didapatkan rata-rata lebar hidung sebesar 38.790, rata-rata panjang hidung sebesar 45.490 serta pengukuran nasal index didapatkan rata-rata 85.6416. Kesimpulan: Nasal indeks dapat digunakan untuk membantu menentukan identitas personal, terutama perbedaan ras, etnis, dan jenis kelamin. Hasil nasal index pada populasi bali aga di Desa Tenganan adalah jenis hidung Platyrrhine (hidung lebar).